Psychoactive Substance Use among Adolescents in Ado-Ekiti, Nigeria: Prevalence and Association with Anxiety and Depression - J. A., Akinbote,; O. O., Omigbodun (International Journal of Innovative Research in Medical Science, 2018)
Psychoactive substance use among adolescents is a global public health problem and a serious concern for mental health professionals especially when co-morbid with anxiety and depression. The current study determined the prevalence of adolescents’ psychoactive substance use and its association with anxiety, depression and sociodemographic correlates. Participants (n=1059) completed the Socio-demographic Data Schedule, the World Health Organization (WHO) Student Drug Use Questionnaire and the Hospital Anxiety and Depression Scale. The lifetime prevalence of adolescents’ psychoactive substance use was 57.2%. Logistic regression revealed that adolescents’ psychoactive substance use was increased three-fold by anxiety and it was significantly and independently predicted by older age, poor academic performance, family background, low social class and parental drug use (p< 0.05). This suggests that anxiety among other factors should be particularly sought among adolescents with substance use problems.